Analisis Unsur Intrinsik Dari Gurindam Dua Belas Pasal 1 Karya Raja Ali Haji - Ismaya Fauziah; Sri Lasmawati; Livia Sinta Paramanik (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to analyze the intrinsic elements contained in Gurindam Dua Belas Article 1 by Raja Ali Haji. Intrinsic elements consist of physical elements and mental elements. The background to the creation of Gurindam Dua Belas was Raja Ali Haji's concern about the living conditions of the Malay people at that time, so he created a literary work as a moral responsibility to defend and maintain religion and customs. This research uses a qualitative descriptive method with text content analysis techniques, researchers collect data by analyzing the text content contained in Gurindam Dua Belas Article 1. The results of this research conclude that the intrinsic elements of Gurindam Dua Belas article 1 contain religious advice, namely the importance of religion as a basis. life. The obligation to hold religion as one's main identity, without religion humans lose the meaning of life. The importance of knowing God, oneself, the world and the afterlife in order to understand life correctly and wisely. Carry out all of Allah's commands and stay away from His prohibitions, because life in this world is only temporary and eternal life is in the afterlife. Gurindam is not only a literary work, but also a guide to human life. It is hoped that the results of this research will provide benefits for the development of literary studies in Indonesia, especially understanding the intrinsic elements in the analysis of Gurindam literary works.